Newborn screening: a disease-changing intervention for glutaric aciduria type 1 - Boy, Nikolas; Heringer-Seifert, Jana; Hoffmann, Georg F.; Garbade, Sven; Kölker, Stefan (Annals of neurology, 2018)
Objective: Untreated individuals with glutaric aciduria type 1 (GA1) commonly present with a complex, predominantly dystonic movement disorder (MD) following acute or insidious onset striatal damage. Implementation of GA1 into newborn screening (NBS) programs has improved the short-term outcome. It remains unclear, however, whether NBS changes the long-term outcome and which variables are predictive. Methods: This prospective, observational, multicenter study includes 87 patients identified by NBS, 4 patients missed by NBS, and 3 women with GA1 identified by positive NBS results of their unaffected children. Results: The study population comprises 98.3% of individuals with GA1 identified by NBS in Germany during 1999–2016. Overall, cumulative sensitivity of NBS is 95.6%, but it is lower (84%) for patients with low excreter phenotype. The neurologic outcome of patients missed by NBS is as poor as in the pre-NBS era, and the clinical phenotype of diagnosed patients depends on the quality of therapeutic interventions rather than noninterventional variables. Presymptomatic start of treatment according to current guideline recommendations clearly improves the neurologic outcome (MD: 7% of patients), whereas delayed emergency treatment results in acute onset MD (100%), and deviations from maintenance treatment increase the risk of insidious onset MD (50%). Independent of the neurologic phenotype, kidney function tends to decline with age, a nonneurologic manifestation not predicted by any variable included in this study. Interpretation: NBS is a beneficial, disease-changing intervention for GA1. However, improved neurologic outcome critically depends on adherence to recommended therapy, whereas kidney dysfunction does not appear to be impacted by recommended therapy. Ann Neurol 2018;83:970–979